Role of halal auditors and challenges in managing halal certification - Muhammad, Muhammad Arif (2018)
Halal Certification has become a standard that has been used widely in Malaysia especially in industry. This halal certification has been managed by Malaysian halal body authorities which are Department of Islamic Development Malaysia (JAKIM) and State Islamic Religious Department (JAIN). A Halal Auditors is a person who reviews and handles an audit session before the services or products can be certified Halal. The aim of this qualitative study (conducted through an in-depth interview) is to explore the role of Halal Auditors and its challenges in managing halal certification process in Klang Valley area. To fulfill this objective of this study, four different types of informants were interviewed. They are Halal Auditors, halal certification panel, Halal Executives, and personnel of Ministry of Science, Technology and Innovation (MOSTI). The result of this study revealed challenges faced by Halal Auditors such as competition from another foreign certification bodies, lack of manpower, qualification of a halal auditor, problems in MYeHALAL system, the introduction of the new scheme and the challenges in reviewing halal certification application. Halal Auditors also shared the initiatives made by JAKIM to improve their performance in halal certification body. The second research question was answered through an in-depth interview with Halal Certification Panel. He gave a few suggestions for improvement regarding infrastructure for Malaysia halal certification body in terms of the manpower and resources for the mobile halal certification process. The Halal Executives voiced out their dissatisfaction during halal certification process especially when dealing with MYeHALAL, a system for halal certification application process, the challenges of Halal Auditors when make decision, delay in reviewing process, lack of proper guideline in Malaysia Halal Certification especially in developing Halal Assurance System (HAS), a competition from foreign halal certification bodies for Halal Auditors in giving recognition of the profession. In terms of practical implications, the findings of this study can be used as a baseline data for any policy invention, improvement or advocacy efforts related to halal certification process in Malaysia. The original contribution of this study is to highlight how important the role of Halal Auditors for halal certification process and how they can give impact to the industry performance in Malaysia. This study is also in line with the National Transformation 2050 (TN50) and Industry Revolution 4.0 (IR 4.0) to uphold the profession of the Halal Auditors as a public servant.